1995
DOI: 10.1021/ac00098a014
|View full text |Cite
|
Sign up to set email alerts
|

Microfabrication and Characterization of Diaphorase-Patterned Surfaces by Scanning Electrochemical Microscopy

Abstract: Scanning electrochemical microscopy (SECM) was used to microfabricate and quantify diaphorase-pattemed glass surfaces. Deactivated circular and linear micropattems were produced at diaphorase-immobilized substrates by a localized surface reaction. The oxidation of Br~and Clã t a microelectrode generated a reactive species which deactivated the localized enzyme molecules at the substrate. The diaphorase-pattemed surfaces were characterized by SECM on the basis of detection of catalytic current of ferrocenylmeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
91
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(96 citation statements)
references
References 0 publications
2
91
0
3
Order By: Relevance
“…For the single particle measurements, a lab-made Pt microprobe was used to make electrical connection with a needlelike LiCoO 2 particle; details of the fabrication procedure have been described elsewhere. 31 Before the measurement, the Pt microprobe was subjected to cyclic voltammetry in an aqueous 0.5 M H 2 SO 4 solution for the cleaning. The single particle measurements were carried out in a super-dry room at room temperature (298 K).…”
Section: Methodsmentioning
confidence: 99%
“…For the single particle measurements, a lab-made Pt microprobe was used to make electrical connection with a needlelike LiCoO 2 particle; details of the fabrication procedure have been described elsewhere. 31 Before the measurement, the Pt microprobe was subjected to cyclic voltammetry in an aqueous 0.5 M H 2 SO 4 solution for the cleaning. The single particle measurements were carried out in a super-dry room at room temperature (298 K).…”
Section: Methodsmentioning
confidence: 99%
“…Matsue and co-workers [66] fabricated and characterised diaphorase-patterned surfaces at the micrometre level. Additional work by Shiku et al [67] found that by coupling SECM with the enzyme-linked immunosorbent assay (ELISA) technique, detection levels as low as 10 4 molecules in a single 20 mm radius spot could be obtained for a carcinoembryonic antigen.…”
Section: Redox Processes On Biological Surfacesmentioning
confidence: 99%
“…[1][2][3][4][5][6] The electrolytic generation of a reactive compound at the microelectrode (i.e. the SECM probe) allows the chemically well-defined transformation of various materials and layers that can be quantitatively controlled by adjusting the working distance, electrolysis current, and electrolysis time.…”
mentioning
confidence: 99%
“…Br 2 and HOBr act as oxidants and have been used for semiconductor etching, [1,8] polyaniline deposition, [3] and the deactivation of enzyme layers. [2] Other probe-generated reagents include metal ions for metal deposition, [9,10] catalytically active metal ions, [11] and aryl diazonium salts. [6,12] The pH shift associated with nitrite oxidation was applied in the local etching of a thin Ni coating on a gold substrate in a chemical lens.…”
mentioning
confidence: 99%